Growing up Jim Crow : how Black and White southern children learned race - Ritterhouse, Jennifer, 1970- (Chapel Hill : University of North Carolina, 2006)
In the segregated South of the early twentieth century, unwritten rules guided every aspect of individual behavior, from how blacks and whites stood, sat, ate, drank, walked, and talked to whether they made eye contact with one another. Jennifer Ritterhouse asks how children learned this racial "etiquette," which was sustained by coercion and the threat of violence. More broadly, she asks how individuals developed racial self-consciousness. Parental instruction was an important factor--both white parents' reinforcement of a white supremacist worldview and black parents' oppositional lessons in respectability and race pride. Children also learned much from their interactions across race lines. The fact that black youths were often eager to stand up for themselves, despite the risks, suggests that the emotional underpinnings of the civil rights movement were in place long before the historical moment when change became possible. Meanwhile, a younger generation of whites continued to enforce traditional patterns of domination and deference in private, while also creating an increasingly elaborate system of segregation in public settings. Exploring relationships between public and private and between segregation, racial etiquette, and racial violence, Growing Up Jim Crow sheds new light on tradition and change in the South and the meanings of segregation within southern culture
Introduction : forgotten alternatives -- The etiquette of race relations -- Carefully taught -- I knew then who I was -- Playing and fighting -- Adolescence -- Conclusion : children of the sun.
Includes bibliographical references (pages 269-291) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: African Americans -- Segregation -- Southern States -- History -- 20th century; Southern States -- Race relations -- History -- 20th century; Race awareness in children -- Southern States -- History -- 20th century; African American children -- Southern States -- Social conditions -- 20th century; Children, White -- Southern States -- Social conditions -- 20th century; African Americans -- Race identity -- Southern States -- History -- 20th century; White people -- Race identity -- Southern States -- History -- 20th century; Etiquette -- Southern States -- Psychological aspects -- History -- 20th century; Noirs américains -- Ségrégation -- États-Unis (Sud) -- Histoire -- 20e siècle.; États-Unis (Sud) -- Relations raciales -- Histoire -- 20e siècle.; Conscience de race chez l'enfant -- États-Unis (Sud) -- Histoire -- 20e siècle.; Enfants noirs américains -- États-Unis (Sud) -- Conditions sociales -- 20e siècle.; Enfants blancs -- États-Unis (Sud) -- Conditions sociales -- 20e siècle.; Noirs américains -- Identité ethnique -- États-Unis (Sud) -- Histoire -- 20e siècle.; SOCIAL SCIENCE -- Ethnic Studies -- African American Studies; African American children -- Social conditions; African Americans -- Race identity; African Americans -- Segregation; Race awareness in children; Race relations; White people -- Race identity; Southern States; Kind; Rassentrennung; Rassendiskriminierung; USA -- Südstaaten; Schwärze; Afro-amerikaner -- historia -- Förenta staterna -- 1900-talet.; Rasism -- historia -- Förenta staterna -- 1900-talet.; Vita -- historia -- Förenta staterna -- 1900-talet.; Barn -- sociala förhållanden -- Förenta staterna -- 1900-talet.; 1900-1999; History; Electronic books